Genomic and Proteomic Characterizations of Sfin-1, a Novel Lytic Phage Infecting Multidrug-Resistant Shigella spp. and Escherichia coli C - Ahamed, SK Tousif; Roy, Banibrata; Basu, Utpal; Dutta, Shanta; Ghosh, A. N.; Bandyopadhyay, Boudhayan; Giri, Nabanita (Frontiers in Microbiology, 2019)
Shigellosis is a public health threat in developed as well as developing countries like India. While antibiotic therapy is the mainstay of treatment for shigellosis, current emergence of multidrug-resistant strains of Shigella spp. has posed the problem more challenging. Lytic bacteriophages which destroy antibiotic resistant Shigella spp. have great potential in this context. In this study we presented the isolation and a detailed characterization of a novel bacteriophage Sfin-1, which shows potent lytic activity against multidrug-resistant isolates of Shigella flexneri, Shigella dysenteriae, Shigella sonnei obtained from clinical specimens from shigellosis patients. It is also active against Escherichia coli C. The purified phage is lytic in nature, exhibited rapid absorption (within 5-10 mins.), a short latent period (within 5-20 mins.) and relatively large (~28 to~146 PFU/cell) burst size. The isolated phage shows stability in a broad pH range and survives an hour at 50°C. Genome sequencing and phylogenetic analyses showed that Sfin-1 is a novel bacteriophage, which is very closely related to T1-like phages. In silico analysis indicates that Sfin-1 genome consists of double stranded linear DNA of 50,403 bp (GC content of 45.2%) encoding 81 potential CDSs, several potential promoters and transcriptional terminators. Under Electron microscopy, Sfin-1 shows morphology characteristics of the family Siphoviridae with an isometric head (61 nm) and a non-contractile tail (155 nm). This is most likely the first report of a lytic bacteriophage that is active against three of the most virulent multidrug-resistant Shigella species and therefore might have a potential role in phage therapy of patients infected with these organisms.